Emergency aid and disaster management in hospitals: Crisis communication - Albay, Ayşe (Nova Science Publishers, Inc., 2025)
The risk of natural disasters occurring at any time in the world has made it mandatory to be prepared for disasters. In Turkiye, plans are made to minimize the damage caused by disasters under the coordination of the Disaster and Emergency Presidency (in Turkish: AFAD). Healthcare organizations, which play an active role, especially in disasters and emergencies, and can even be defined as the main actors in managing the process, prepare a Hospital Disaster and Emergency Plan (HDEP) to effectively manage crises that may arise in emergencies and disasters. Disaster management in hospitals is important to ensure the safety and well-being of both patients and employees in emergency and unexpected situations. With the successful implementation of disaster management in hospitals, patient safety can be ensured, the welfare of healthcare personnel can be sustained, infrastructure can be protected, resources can be distributed in a balanced manner, effective communication can be realized, mass casualties can be responded to quickly, and thus the social impact of disasters can be minimized by maintaining public morale and confidence. As a classic crisis communication environment, emergencies or disasters create an air of panic in both internal and external stakeholders, and the management of the process becomes difficult due to this panic. In case of panic, proper management of the emergency or disaster by the ten key management teams identified in the Hospital Emergency and Disaster Plan is important to minimize the damage. Among the ten basic management positions, the Public Relations Officer is responsible for communicating information to internal and external stakeholders, including staff, patients, patients' relatives, the media, and the whole world's public opinion, with the approval of the HDEP President, can play a key role in crisis management by providing effective crisis communication. In disasters and emergencies, crisis communication is important to disseminate information in a timely manner, reduce confusion and panic, build trust, coordinate response efforts, facilitate cooperation, prevent misinformation, promote preparedness, and address public concerns. Therefore, the choice of tools to use to inform the public during a disaster or emergency is very important. In today's technological world, mass media tools that enable interactive communication are frequently preferred by the masses to obtain information about disasters and emergencies. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Crisis communication; Disaster; Disaster management in hospitals; Health organizations; Mass media